Basic Health Services During a Pandemic: From Leadership to Innovation and Optimization of Public Health Degrees - Imam Jayanto; Rustandi Rustandi; Fadli Fadli; A. Nururrochman Hidayatulloh; Ade Iskandar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This paperwork was done to get accurate information about the basics of public health services during a pandemic, from innovative leadership efforts to optimizing public services under challenging times. Our data were obtained from various health information sources published from 2010 to 2001. After that, we carried out various data coding studies, evaluating interpretations and drawing valid conclusions that we were able to answer the questions correctly. Based on the study and discussion of these findings, we can state that the Government must build innovative and optimal leadership when the community needs more prime and core public services. Thus, we believe that this study has answered the core problem. We sought the literature using electronic to several international publications that discussed this sues. Finally, after discussing the result, we can draw our finding is that the Government, through the Department of Health, has put strong leadership over the Covid-19 pandemic.